1998
DOI: 10.1046/j.1365-2958.1998.01094.x
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of expression of the amino acid transporter gene BAP3 in Saccharomyces cerevisiae

Abstract: SummaryThe BAP3 gene of Saccharomyces cerevisiae encodes a protein with a high similarity to the BAP2 gene product, a high-affinity permease for branched-chain amino acids. In this paper, we show that, like BAP2, the expression of the BAP3 gene in S. cerevisiae is induced by the addition of branched-chain amino acids to the medium. Unexpectedly, most other naturally occurring L-amino acids found in proteins (with the exception of proline, lysine, arginine and histidine) have the same effect on the expression o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
51
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(54 citation statements)
references
References 27 publications
(37 reference statements)
3
51
0
Order By: Relevance
“…This pathway appears to be strikingly simple. Despite extensive genetic screens carried out in several independent laboratories (Ljungdahl et al 1992;Grauslund et al 1995;Didion et al 1996;de Boer et al 1998;Jør-gensen et al 1998;Bernard and André 2001a;Forsberg et al 2001), additional components have not previously been identified. A potential explanation for the lack of additional components being identified is the redundant and overlapping activities of Stp1p and Stp2p.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This pathway appears to be strikingly simple. Despite extensive genetic screens carried out in several independent laboratories (Ljungdahl et al 1992;Grauslund et al 1995;Didion et al 1996;de Boer et al 1998;Jør-gensen et al 1998;Bernard and André 2001a;Forsberg et al 2001), additional components have not previously been identified. A potential explanation for the lack of additional components being identified is the redundant and overlapping activities of Stp1p and Stp2p.…”
Section: Discussionmentioning
confidence: 99%
“…In detailed studies focused on the promoters of BAP2 and BAP3, an aminoacid-dependent upstream activating sequence (UAS aa ) was identified (de Boer et al 1998). Both Stp1p and Stp2p are able to bind DNA fragments containing the UAS aa (de Boer et al 2000;Nielsen et al 2001).…”
mentioning
confidence: 99%
“…The region bound by the Cup9p repressor has been narrowed to the region spanning À897 to À448 [34], relative to the PTR2 start codon. In addition, a predicted amino acid-dependent upstream activator sequence (UAS AA ) is located between À777 and À760 [69]. Genomic DNA was prepared using the ''smash and grab'' technique [70].…”
Section: Methodsmentioning
confidence: 99%
“…Upon induction by extracellular amino acids, the SPS sensor catalyzes an endoproteolytic processing event that cleaves the regulatory N-terminal domains. The shorter forms of Stp1 and Stp2 efficiently target to the nucleus where they bind promoters of a limited set of genes, including a subset of broad-specificity amino acid permeases (cluster 1, Table 4) and the peptide transporter Ptr2 (Didion et al 1996(Didion et al , 1998de Boer et al 1998de Boer et al , 2000Iraqui et al 1999;Klasson et al 1999;Wielemans et al 2010;Tumusiime et al 2011).…”
Section: Pathway Genesmentioning
confidence: 99%